Effects of applying blended learning based on the ADDIE model in nursing staff training on improving theoretical and practical operational aspects - Luo, Runfen; Li, Jing; Zhang, Xiaoni; Tian, Dan; Zhang, Yi (Frontiers in Medicine, 2024)
Objective: To assess the impact of blended learning, based on the ADDIE model, on theoretical and practical aspects of nursing staff training. Methods: Retrospective analysis of data from 87 nursing staff members in Xi'an Qinhuang Hospital divided into control (n=43) and observation (n=44) groups. The control group received conventional training, while the observation group underwent blended learning. Comparative analysis included theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction. Results: The observation group showed significantly higher theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction compared to the control group (P<0.05). Conclusion: Blended learning based on the ADDIE model enhances nursing staff training outcomes, improving theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction. This approach presents a promising method for enhancing nursing education and warrants further implementation in clinical settings.